Air Pollution Particulate Matter Amplifies White Matter Vascular Pathology and Demyelination Caused by Hypoperfusion - Huuskonen, Mikko T.; Liu, Qinghai; Lamorie-Foote, Krista; Shkirkova, Kristina; Connor, Michelle; Patel, Arati; Montagne, Axel; Baertsch, Hans; Sioutas, Constantinos; Morgan, Todd E.; Finch, Caleb E.; Zlokovic, Berislav V.; et al. (Frontiers in Immunology, 2021)
Cerebrovascular pathologies are commonly associated with dementia. Because air pollution increases arterial disease in humans and rodent models, we hypothesized that air pollution would also contribute to brain vascular dysfunction. We examined the effects of exposing mice to nanoparticulate matter (nPM; aerodynamic diameter ≤200 nm) from urban traffic and interactions with cerebral hypoperfusion. C57BL/6 mice were exposed to filtered air or nPM with and without bilateral carotid artery stenosis (BCAS) and analyzed by multiparametric MRI and histochemistry. Exposure to nPM alone did not alter regional cerebral blood flow (CBF) or blood brain barrier (BBB) integrity. However, nPM worsened the white matter hypoperfusion (decreased CBF on DSC-MRI) and exacerbated the BBB permeability (extravascular IgG deposits) resulting from BCAS. White matter MRI diffusion metrics were abnormal in mice subjected to cerebral hypoperfusion and worsened by combined nPM+BCAS. Axonal density was reduced equally in the BCAS cohorts regardless of nPM status, whereas nPM exposure caused demyelination in the white matter with or without cerebral hypoperfusion. In summary, air pollution nPM exacerbates cerebrovascular pathology and demyelination in the setting of cerebral hypoperfusion, suggesting that air pollution exposure can augment underlying cerebrovascular contributions to cognitive loss and dementia in susceptible elderly populations.